The concept of leadership and constitution of a country from the Islamic and Malay archipelago perspectives according to Taj Al Salatin manuscript - Nordin, Shahrul Anuar; Mohamad Suhaimy, Khairul Azman; Abdul Rahim, Mohd Hisyam; Borham, Abdul Shakor (Penerbit UTHM, 2020)
The concept of leadership has been present eversince the dawn of time, with scholars steering broad studies from various directions and viewpoints, which were then formed into literary works. In the Malay Archipelago, Taj al-Salatin manuscript (1603M) is extensively recognised as a masterwork that emphasised leadership qualities from the Islamic viewpoint. This study was conducted to recognise the author’s notions on Islamic leadership in the context of Malay Archipelago, using descriptive method by analysing the manuscript. The results revealed that leaders and leadership are deliberated, as a decree from Allah SWT. Good rulers must be competent, with higher knowledge and morals than their followers. Taj al-Salatin presents the indication that rulers should exercise Tasawwuf, which among its practises take account of unceasing self reminder of death, rejecting desires and lust, and prioritising remembrance of Allah. In his manuscript, Bukhari al-Jauhari presents the idea, optimism and the notion of “rulers are perfect beings”, which personifies the concept of Tauhid and espouses noble character for universal civilisation. A ruler of a country should at all times stand on the grounds of good moral standards and the people are led towards generating a peaceful, thriving and blissful nation.